Case Description of Oral Cavity Hard Tissue Disease in Banjarmasin 2017-2020 - Muhammad Yanuar Ichrom Nahzi; Nida Amalia; Ferdy Rijaldi (Berkala Kedokteran, 2022)
Disease that rank first from the list of ten major diseases that are often complained by Indonesian people is oral cavity diseases. The Hard Tissue of oral cavity lesions can be in the form od caries, periodontal disease, periapical abnormalities, cysts, and tumor in the oral cavity. Based on the Riset Kesehatan Dasar (Riskesdas) in 2018 the prevalence of dental and oral problem in Indonesia in South Kalimantan was 59,6%. The purpose of this study is to determine the description of oral hard tissue lesions in Banjarmasin city in 2017-2020. This research is descriptive study using a cross sectional approach. The variables on this study were oral hard tissue disease and gender, the data used were secondary data that obtained from the recording and reporting of the LB-1 form at Banjarmasin Community Health Center. The results showed that the most common type of disease on oral hard tissue case in 2017-2020 was pulp and periapical tissue disease, in 2017 it was 12,640 cases (78.37%), in 2018 it was 18,184 cases (51,45%). In 2019 it was 22,493 cases (57.07%) and in 2020 it was 3,220 cases (58.59%). In 2017, the most cases were in men with total of 7,887 cases (62.50%),while in 2018, 2019, and 2020, the most cases were in women with a total of 11,621 cases (64,29%), 14,285 cases (63.51%) and 1,892 cases (58.76%). It is necessary to prevent oral hard tissue disease, especially in pulp and periapical tissue disease.